Digital-Based Evaluation in Arabic Writing: Integrating Educaplay to Enhance Students’ Writing Skills - Syifa Aulia; Saefullah Azhari (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
The teaching of Arabic writing often faces challenges, particularly students’ low motivation, limited vocabulary mastery, and the lack of interactive digital evaluation tools. This study aims to examine the use of Educaplay as a digital-based evaluation medium to enhance students’ Arabic writing skills. A mixed-method approach was employed, involving observation, questionnaires, and pre-test and post-test assessments administered to 40 tenth-grade students. The findings show a clear improvement in students’ writing performance, as indicated by higher post-test scores compared to pre-test results. Improvements were observed in creativity, text organization, vocabulary use, and grammatical accuracy. In addition, students expressed positive perceptions regarding the usability, interactivity, and motivational impact of Educaplay. These findings imply that integrating interactive digital evaluation tools such as Educaplay can effectively support the development of Arabic writing skills and promote more engaging learning environments.